Biological properties and in silico studies of thiazolopyrimidine derivatives active against visceral and cutaneous Leishmania spp. amastigote forms - Gulsah Bayraktar; Pascal Marchand; Euzébio Guimarães Barbosa; Marilia Cecilia da Silva; Karen Cacilda Weber; Sandrine Cojean; Merve Saylam; Huseyin Istanbullu (European Journal of Medicinal Chemistry Reports)
Visceral leishmaniasis, the most severe form of the disease, is caused by L. donovani and L. infantum parasites; cutaneous leishmaniasis is the most common endemic form of leishmaniasis and mainly caused by L. tropica and L. major. We have previously described a series of thiazolopyrimidine derivatives and reported their antipromastigote activities against various parasites. In this study, we also investigated their activities against L. donovani and L. major axenic amastigotes, intramacrophage amastigotes and cytotoxicity on macrophages to assess selectivity. As a result, five of the compounds tested showed no cytotoxicity on the macrophage cell line; their anti-amastigote activity was close to the positive control, miltefosine. These results confirm the antileishmanial activity of the thiazolopyrimidine scaffold and demonstrate that this may be a starting point for the generation of new lead compounds for treating visceral leishmaniasis and cutaneous leishmaniasis. To elucidate the mechanism of action, we also performed several ligand- and structure-based in silico studies.